Sanctity as literature in late medieval Britain - Contzen, Eva von; Bernau, Anke (Manchester : Manchester University Press, 2016)
This title explores how sanctity and questions of literariness are intertwined across a range of medieval genres.
12. Afterword: calendar time in balade form, Catherine SanokBibliography; Index
Previously issued in print: 2015.
Includes bibliographical references and index.
Online resource; title from home page (viewed on April 21, 2016).
OCLC control number change - Master record variable field(s) change: 050, 072
Keywords: English literature -- Middle English, 1100-1500 -- History and criticism; Religion in literature; Saints in literature; English literature -- Middle English; Religion in literature; Saints in literature; LITERARY CRITICISM / European / English, Irish, Scottish, Welsh; 1100-1500; Criticism, interpretation, etc; Electronic books